The Relationship Between the Brain and First Language Acquisition in Children - Husein, Ahmad; Nurhidayah, Nurhidayah; Sidik, Anwar (Universitas Al-Amien Prenduan, 2025)
This study examines the relationship between brain development and first language acquisition in children aged 0–3 years from a neurolinguistic and developmental psychology perspective. Early language acquisition is closely associated with the maturation of language-related brain regions, including Broca’s area, Wernicke’s area, and broader associative neural networks. This research aims to analyze how neural development supports the acquisition of phonological, morphological, and syntactic abilities during early childhood. The study employs a qualitative descriptive approach by observing and analyzing linguistic data from children across different age groups (0–1, 1–2, and 2–3 years). The findings indicate that early vocalizations such as crying and babbling reflect the maturation of neuromotor and auditory systems, which gradually develop into meaningful linguistic structures as neural and cognitive capacities increase. In addition, environmental linguistic input plays a significant role in strengthening neural representations of language during the critical period of development. The originality of this study lies in its integrative framework, which synthesizes neurolinguistic evidence with developmental psychology to provide a comprehensive explanation of first language acquisition. This research contributes both theoretically and practically by offering insights into the role of brain structure and function in early language development and by highlighting implications for early language stimulation.